SENAM OTAK MEMPENGARUHI DEMENSIA PADA LANSIA BRAIN EXERCISE AFFECTS DEMENTIA IN THE ELDERLY - Elvipson Sinaga; Khairunnisa Batubara (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Cognitive decline interferes with activities of daily living and social activities in the elderly. One of the physical exercises that can be applied in order to delay cognitive function is by means of brain exercise because it is believed to provide much-needed stimulation for dementia patients. This study aims to determine the effect of brain exercise on short-term memory (Dementia) in the elderly at the Sibolangit Health Center, Sibolangit District, Deli Serdang Regency. The design of this research is Quasi Experiment Design using One-group pretest posttest design. The sample in this study were 49 respondents using purposive sampling. Data analysis using Paired Sample T-Test. The results showed a P-value of 0.0001 (P-value <0.05) so it can be said that there were changes before and after carrying out brain exercise in the elderly at the Sibolangit Health Center, Sibolangit District, Deliserdang Regency. Brain exercise is one of the physical activity therapies that can improve the memory of the elderly or often also called dementia.